Challenging authoritarianism in Southeast Asia comparing Indonesia and Malaysia - Heryanto, Ariel; Mandal, Sumit Kumar (Politics in Asia series., 2003)
Challenging Authoritarianism in Southeast Asia is one of the first substantial comparative studies of contemporary Indonesia and Malaysia, homes to the world's largest Muslim population. Following the collapse of New Order rule in Indonesia in 1998, this book provides an in-depth examination of anti-authoritarian forces in contemporary Indonesia and Malaysia, assessing their problems and prospects. The authors discuss the roles played by women, public intellectuals, arts workers, industrial workers as well as environmental and Islamic activists. They explore how different forms of authoritarianism in the two countries affect the prospects of democratization, and examine the impact and legacy of the diverse social and political protests in Indonesia and Malaysia in the late 1990s.